The centipede fauna (Chilopoda) of the island of Cyprus, with one new lithobiomorph species - Simaiakis, Stylianos Michail; Zapparoli, Marzio; Minelli, Alessandro; Bonato, Lucio (Zootaxa, 2013)
The centipede (Chilopoda) fauna of Cyprus, which was almost unknown, has been analysed by examining more than 1,800 specimens sampled from 185 sites, besides revising critically the few published data. A total of 26 species are listed and discussed (1 Scutigeromorpha, 9 Lithobiomorpha, 3 Scolopendromorpha, 13 Geophilomorpha), 21 of which are new to the island, i.e. Scutigera coleoptrata (Linnaeus, 1758), Lithobius (Ezembius) parvicornis (Porat, 1893), L. (E.) pamukkalensis Matic, 1980, L. (E.) zeylanus (Chamberlin, 1952), L. (Lithobius) carinatus L. Koch, 1862, L. (L.) erythrocephalus C.L. Koch, 1847, L. (Lithobius?) anderssoni n. sp., L. (Monotarsobius) ferganensis Trotzina, 1880, Cryptops (Cryptops) kosswigi (Chamberlin, 1952), C. (C.) cf. trisulcatus Brölemann, 1902, Dignathodon microcephalus (Lucas, 1846), Henia (Meinertia) bicarinata (Meinert, 1870), Geophilus cf. alpinus Meinert, 1870, G. cf. carpophagus Leach, 1815, Pachymerium ferrugineum (C.L. Koch, 1835), Schizotaenia sp., Stenotaenia naxia (Verhoeff, 1901), Thracophilus cilicius Attems, 1947, Nannophilus eximius (Meinert, 1870) and Schendyla cf. nemorensis (C.L. Koch, 1837), and another unidentified species of Schendylidae . As far as known, Lithobius anderssoni n. sp. is endemic to the island. Geographic distribution in Cyprus and ecological notes are given for each species. Taxonomic remarks are given for some species.